The association between teachers' positive instructional emotions and job performance: Work engagement as a mediator - Ümit Dilekçi; İbrahim Limon; Abdullah Manap; Abdulmohsen Mohammed Abdullah Alkhulayfi; Murat Yıldırım (Acta Psychologica)
This study investigated the mediating role of work engagement in the relationship between teachers' positive instructional emotions and job performance in the Turkish educational system. Using a cross-sectional design, a sample of 413 preschool to high school teachers completed an online survey measuring their instructional emotions, engagement, and job performance. The results suggested that teachers' positive instructional emotions significantly predicted both their job performance (β = 0.29; p˂0.001) and work engagement (β = 0.66; p˂0.001). Work engagement was a significant predictor of job performance (β = 0.46; p˂0.001) and mediated the relationship between positive instructional emotions and job performance (BootLLC = 0.23 and BootULCI = 0.37; BootSE = 0.04; Effect = 0.30). These findings highlight the crucial role of teachers' emotional experiences in shaping their professional effectiveness. The study contributes to the existing literature by demonstrating the psychological mechanisms that enhance teacher performance, particularly in non-Western educational contexts. The results suggest that intervention programs to improve teacher effectiveness should focus on fostering positive instructional emotions and increasing work engagement, which may ultimately benefit student learning outcomes.